Management of patients with antiphospholipid antibodies: what to do in laboratory scenarios that do not fit the guidelines. Issue 5 (4th May 2021) - Pires Da Rosa, Gilberto; Rodríguez-Pintó, Ignasi; Cervera, Ricard; Espinosa, Gerard
ABSTRACT: Introduction : Some patients with positive antiphospholipid antibodies (aPL) have not been included in randomized clinical trials or observational registries and, therefore, information on their risk of obstetric or thrombotic recurrence and optimal treatment is scarce. Areas covered : In the present review, the existing evidence regarding the management of two laboratory scenarios not covered by the guidelines is presented: (1) patients with antiphospholipid syndrome (APS) clinical manifestations and aPL positivity not fulfilling APS laboratory criteria, and (2) the possibility of discontinuing anticoagulation in APS patients whose aPL become persistently negative. Expert opinion : Growing evidence suggests a role for low titers and 'non-criteria' aPL, especially in obstetric APS. Treatment is not formally recommended but might be considered according to the individual's risk profile. Regarding the question of whether or not to discontinue anticoagulants after the 'spontaneous' disappearance of aPL, there is no definite answer. Retrospective studies seem to suggest that withdrawal of anticoagulation could be safe in certain patients with APS, especially in those with a first provoked venous thrombosis and whose aPL became persistently negative during follow-up. Still, before the withdrawal can be recommended in routine clinical practice, multicenter and prospective studies are required to validate this hypothesis.